PENGARUH CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN: Studi pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2012 -2016 - Atiningsih, Suci; Suparwati, Yohana Kus (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
This study aims to determine the effect of managerial ownership, ownership, independent board of directors, audit committee, and leverage on the integrity of financial statements on mining companies listed on the Indonesia Stock Exchange in 2012 -2016. The population used in this research is mining companies listed on the Indonesia Stock Exchange 2012 -2016 period. The samplingtechnique used was purposive sampling.The number of samples is 155 companies. The analysis method used is multiple linier regression analysis. The result of this research are : managerial ownership and institutional ownership have a positive effect on the integrity of financial statements. Independent commissioners and audit committees have no effect on the integrity of financial statements. Leverage has a negative effect on the integrity of financial statements.